Building a culture of impact in an international agricultural research organization: Process and reflective learning. Issue 2 (9th November 2018) - Blundo-Canto, Genowefa; Triomphe, Bernard; Faure, Guy; Barret, Danielle; de Romemont, Aurelle; Hainzelin, Etienne
Abstract: Most agricultural research organizations strive to address societal challenges and contribute to positive societal impacts. Fulfilling this ambition involves embedding a culture of impact in organizational culture, which, in our view, entails three main elements: understanding the role of the research community in contributing to impacts over the long term within the systems in which it operates; equipping researchers to support positive change; and implementing strategies that allow the culture of impact to percolate at various levels of the organization. To build just such a culture, in the past 8 years, Cirad, the French Agricultural Research Center for International Development, embarked on a transformational process, from which we draw key lessons. Building a culture of impact requires fostering transdisciplinary dialogue on the multiple roles of researchers, on their contribution to societal impacts, and on the relevance of this reflection. This involves adapting from pre-existing visions, interactions, and practices. Formalization in the organization's strategy and the action of leading change agents foster its institutionalization. Strengthening capacity to build shared visions of change and collective processes in research design, implementation, and evaluation while respecting the diversity of profiles and approaches in the organization favors appropriation. This requires adequate funding at the project, institutional and funding bodies level, and targeted communication to ensure buy-in by internal and external change agents. We argue that a culture of impact is a reflective culture and long-term dynamics that aims to overcome the dichotomy between research and development and bring agricultural research closer to societal needs.